The Effect of Case-Based Learning on Students’ Writing Performance in EFL Contexts - Ilham, Ilham (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study examines the effect of Case-Based Learning (CBL) on students' writing skills in the context of English as a Foreign Language (EFL) through the Systematic Literature Review method of research published in the last ten years in Scopus, DOAJ, and Google Scholar databases. The results show that CBL effectively improves writing skills, especially in the aspects of coherence, grammar, and paragraph organization. By engaging students in real-world scenarios, this method encourages logical and systematic organization of arguments and develops critical thinking skills, creativity, and analytical abilities. The integration of CBL with the Process Writing Approach (PWA) strengthens the text drafting and revision process, while peer review activities contribute to improving grammatical accuracy. In addition, the CBL method showed flexibility across different educational levels, improving negotiation text writing skills in vocational schools and analytical ability in higher education. Compared to traditional methods, CBL encourages deep engagement with the material and the application of theory into practice, although its success largely depends on the quality of the cases, the competence of the facilitators, and institutional support. Challenges encountered include the need for additional guidance for students who struggle to grasp abstract concepts and the provision of adequate infrastructure for technology integration. Future research is recommended to explore the long-term impact of CBL on retention of writing skills, its effectiveness across different language proficiency levels, as well as the role of digital technology in supporting the learning process. With adequate institutional support and comprehensive implementation strategies, CBL can be an effective and sustainable method in improving writing skills in EFL contexts.